A Survey of Econometric Methods for Mixed-Frequency Data - Claudia Foroni; Massimiliano Marcellino (Norges Bank, 2013)
The development of models for variables sampled at different frequencies has attracted substantial interest in the recent econometric literature. In this paper we provide an overview of the most common techniques, including bridge equations, MIxed DAta Sampling (MIDAS) models, mixed frequency VARs, and mixed frequency factor models. We also consider alternative techniques for handling the ragged edge of the data, due to asynchronous publication. Finally, we survey the main empirical applications based on alternative mixed frequency models.
hdl:11250/2496703
Keywords: E37; C53; 330; VAR; MIDAS model; mixed frequency data; nowcasting; forecasting